2018
DOI: 10.1152/ajplung.00357.2017
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an alveolar epithelial type II cell line from induced pluripotent stem cells

Abstract: Differentiation of primary alveolar type II epithelial cells (AEC type II) to AEC type I in culture is a major barrier in the study of the alveolar epithelium in vitro. The establishment of an AEC type II cell line derived from induced pluripotent stem cells (iPSC) represents a novel opportunity to study alveolar epithelial cell biology, for instance in the context of lung injury, fibrosis and repair. In the present study, we generated long lasting AECII from iPSC (iPSC-AEC). Long lasting iPSC-AECII (LL)-iPSC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…In summary, our study provides support for the use of hiPSC in generating relatively mature populations of AEC2 and both confirms and extends previous studies in this area 18,20,22,23,26,35,39 . In addition, the study shows that iAEC2 can be used to study epithelial repair processes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In summary, our study provides support for the use of hiPSC in generating relatively mature populations of AEC2 and both confirms and extends previous studies in this area 18,20,22,23,26,35,39 . In addition, the study shows that iAEC2 can be used to study epithelial repair processes.…”
Section: Discussionsupporting
confidence: 89%
“…In iAEC2 cultures, and not in pAEC2 cultures, this treatment was accompanied by an increase in cells positive for PDPN, a marker associated with an AEC1 phenotype, with a concomitant decrease in pro-SFTPC positive cells at the wound edge. Before our study, other groups had reported the generation of AEC2 from embryonic- 16,17 and induced pluripotent stem cells [18][19][20][21][22][23][24][25][26] . Our protocol was largely based on these published protocols, with some modifications that improved purity and maturity in our hiPSC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, several animal models of IPF, including bleomycin-induced lung fibrosis, fail to fully recapitulate IPF as seen in patients. Despite this, basic science contributes to the field by generating novel in vitro and in vivo models such as induced pluripotent stem cell-generated AECs [129], precision-cut ex vivo lung models [130], lung-on-chip technologies [131] and gene-engineered mice. These systems will be important to appropriately study lung fibrosis and develop effective therapies in the future.…”
Section: Limitations In Basic Researchmentioning
confidence: 99%